Pengaruh Konflik Kerja, Lingkungan Kerja, Dan Pengembangan Sdm Terhadap Kinerja Pegawai Pada Dinas Perhubungan Labuhanbatu - Kiki Arianto; Bayu Eko Broto; Raja Saul Marto Hendry (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to analyze the effect of Work Conflict, Work Environment and Human Resources Development on the Performance of Shopping Employees in Wholesale Sembako Mrs. Ervina, Aek Paing Tengah Village To determine the effect of Work Conflict, Work Environment and Human Resources Development on Employee Performance with a sample of 134 people. The data collection technique was carried out by questionnaire or primary data. The results showed that simultaneously the variables of Work Conflict, Work Environment, and HR Development had a positive and significant effect on Employee Performance with a calculated F value of 11,650 greater than Ftable 2.37 with a significant value of 0.000 <0.05, partially Work Conflict has a positive but insignificant effect on Employee Performance obtained tcount value 0.263 smaller than ttable 1, 65 partially the Work Environment has a positive but insignificant effect on the consumer's decision to buy with t count 1.985 greater than t table 1.65 and the significance value of t is 0.049 < 0.05, partially HR Development has a positive and significant effect on consumer decisions obtained tcount 3.317> t table 1.65 and the significance value of t is 0.001 < 0.05. Keywords: Work Conflict, Work Environment, HR Development, Employee Performance